2008
DOI: 10.1007/s11999-008-0284-6
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy with ATX-S10·Na(II) Inhibits Synovial Sarcoma Cell Growth

Abstract: Photodynamic therapy (PDT) is an effective cancer treatment modality that allows selective destruction of malignant tumor cells. We asked whether PDT could inhibit in vivo and in vitro growth of synovial sarcoma cells. We analyzed PDT using ATX-S10.Na(II) and a diode laser for a synovial sarcoma cell line (SYO-1). Photodynamic therapy with ATX-S10.Na(II) showed an in vitro cytotoxic effect on the cultured SYO-1 cells. The in vitro effect of PDT depended on the treatment concentration of ATX-S10.Na(II) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In 2008 Takeda and coworkers published in vitro and in vivo studies on ATX-S10•Na(II)-PDT of SYO-1 synovial sarcoma cells and tumours and found a dose-dependent inhibition and eradication of cells in vitro, and curation of tumours in athymic mice. The authors also found a significant reduction in local recurrences when treating with ATX-S10•Na(II)-PDT after marginal resection of the subcutaneous tumours [104]. Studies by Jin et al on angiosarcoma, an extremely lethal variant of STS, evaluated effects of Photofrin-PDT in vitro and in vivo.…”
Section: Pdt and Sarcomasmentioning
confidence: 95%
“…In 2008 Takeda and coworkers published in vitro and in vivo studies on ATX-S10•Na(II)-PDT of SYO-1 synovial sarcoma cells and tumours and found a dose-dependent inhibition and eradication of cells in vitro, and curation of tumours in athymic mice. The authors also found a significant reduction in local recurrences when treating with ATX-S10•Na(II)-PDT after marginal resection of the subcutaneous tumours [104]. Studies by Jin et al on angiosarcoma, an extremely lethal variant of STS, evaluated effects of Photofrin-PDT in vitro and in vivo.…”
Section: Pdt and Sarcomasmentioning
confidence: 95%
“…OS leads to poor limb function and shows high local recurrence and metastasis rates. The conventional treatment for bone and soft tissue sarcoma includes surgical resection, chemotherapy, and radiotherapy, which may lead to severely impaired limb function and a high risk of local recurrence [6]. As a novel treatment modality for bone tumors, PDT is used for patients with advanced stage disease or a large tumor that cannot be ablated by surgery, or those who wish to regain excellent limb function after wide tumor resection [7].…”
Section: Introductionmentioning
confidence: 99%
“…The FDA have approved the use of PDT in numerous pathologies like advanced cutaneous T-cell lymphoma, actinic keratosis, basal cell skin cancer, Barrett esophagus, esophageal cancer, non-small cell lung cancer and squamous cell skin cancer. Moreover, other types of cancer and more pathologies such as bacterial infections [116,117] and the cancer studied in this work, synovial sarcoma [118,119], are also under PDT investigations, in addition to the one already described in this thesis, the RA [32,120].…”
Section: Inflammatory Studymentioning
confidence: 99%